Lessons learned from the development of a national registry on dementia care and support based on linked national health and administrative data - Iris van derHeide; Anneke L. Francke; Carola Döpp; Marianne Heins; Hein P. J. vanHout; Robert A. Verheij; Karlijn J. Joling (Wiley, 2024)
Abstract Introduction This paper provides insight into the development of the Dutch Dementia Care and Support Registry and the lessons that can be learned from it. The aim of this Registry was to contribute to quality improvement in dementia care and support. Methods This paper describes how the Registry was set up in four stages, reflecting the four FAIR principles: the selection of data sources (Findability); obtaining access to the selected data sources (Accessibility); data linkage (Interoperability); and the reuse of data (Reusability). Results The linkage of 16 different data sources, including national routine health and administrative data appeared to be technically and legally feasible. The linked data in the Registry offers rich information about (the use of) care for persons with dementia across various healthcare settings, including but not limited to primary care, secondary care, long‐term care and medication use, that cannot be obtained from single data sources. Conclusions A key lesson learned is that in order to reuse the data for quality improvement in practice, it is essential to involve healthcare professionals in setting up the Registry and to guide them in the interpretation of the data.